DRYING CLOSED CORN GRAIN DRYER FLOW IN A COMMERCIAL MIXED - Coradi, P. C.; Milane, L. V.; Andrade, M. G. O.; Camilo, L. J.; Souza, A. H. S. (Revista Brasileira de Engenharia de Biossistemas, 2016)
The objective was to evaluate the effects of drying air temperature (80, 100 and 120 °C) and falling water levels in physical and physicochemical quality of grains of maize (Zea mays L.) in a dryer flow mixed operating of continuous form. The experimental design was completely randomized in a factorial scheme (7x3) (water content x drying temperatures). The reduction of the water content associated with the increased temperature of the drying air reduced length, width, thickness, volume, sphericity and roundness of corn grains. The acid values and the percentage of ash increased with the reduction of water levels, with no differences between the drying air temperatures. The decrease of the water content by increasing the drying air temperature increased electrical conductivity and reduced the germination of grains, with no difference between the temperatures of 100 and 120 °C. It was concluded that the drying process is continuously mixed flow of air and product dryers in the air temperatures at 80 °C in not affected the physical and physical-chemical quality of the corn grains.